Dairy goats ? feeding and milk marketing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Feeding dairy goats, including use of concentrates, marketing goat milk and other goat milk products, and the benefits of goat milk.